A perspective on the efficacy of green gas production via integration of technologies in novel cascading circular bio-systems. (October 2021) - Lin, Richen; O'Shea, Richard; Deng, Chen; Wu, Benteng; Murphy, Jerry D.
Abstract: Presently more energy is sourced from the natural gas grid than the electricity grid in the EU and the US. Furthermore hard-to-abate sectors such as heavy-duty transport are not readily served by electricity. Decarbonised energy systems will require renewable fuels (such as biomethane) to reduce the reliance on fossil-based diesel and natural gas. Anaerobic digestion (AD) is a technology which with other bio-based technologies can effect improved energy conversion and reduction in greenhouse gas (GHG) emissions across sectors beyond energy. Here, an AD-centred cascading circular system with carbon capture and utilisation was proposed by incorporating power to gas (P2G), microbial electrolysis cell (MEC), and digestate valorisation for biochar production. The system as modelled converted CO2 to biomethane and digestate to biochar for CO2 sequestration. This was exemplified through cattle slurry with an annual production of 3.03 billion tons in three studied regions (the EU, China and the US), which was shown to produce a maximum of 2.29 EJ (equivalent to 1.64% of natural gas demand in 2018) of total energy in the form of advanced biofuels (biomethane, bio-oil and syngas) via the AD-MEC system, which was preferable to a conventional AD or an AD-P2G system. The treatment of cattle slurry with AD-MEC led to a combined 397.4 MtCO2 e of GHG emission savings in the three regions. This could contribute to avoiding 2.0% of GHG emissions (total 20.1 GtCO2 e) in the three regions. The sustainability of such a system was shown to be dependent on access to low-carbon and low-cost electricity systems. Graphical abstract: Image 1 Highlights: Anaerobic digestion-centred carbon capture and utilisation technologies are assessed. Anaerobic digestion with microbial electrolysis can almost double biomethane yield. The system is exemplified by cattle slurry as feedstock in the EU, China and the US. The system may supply 1.64% of global natural gas demand in 2018. The system may reduce 2.0% of annual GHG emissions in three studied regions.